Magnetic Functionalized Nanoparticles for Biomedical, Drug Delivery and Imaging Applications - Simon D. Anderson (Nanoscale Research Letters, 2019)
Abstract Medicine is constantly looking for new and improved treatments for diseases, which need to have a high efficacy and be cost-effective, creating a large demand on scientific research to discover such new treatments. One important aspect of any treatment is the ability to be able to target only the illness and not cause harm to another healthy part of the body. For this reason, metallic nanoparticles have been and are currently being extensively researched for their possible medical uses, including medical imaging, antibacterial and antiviral applications. Superparamagnetic metal nanoparticles possess properties that allow them to be directed around the body with a magnetic field or directed to a magnetic implant, which opens up the potential to conjugate various bio-cargos to the nanoparticles that could then be directed for treatment in the body. Here we report on some of the current bio-medical applications of various metal nanoparticles, including single metal nanoparticles, functionalized metal nanoparticles, and core-shell metal nanoparticles using a core of Fe3O4 as well as synthesis methods of these core-shell nanoparticles.